Finan??as e crescimento: o caso dos munic??pios brasileiros - Vicente, Tadeu Siqueira (2017)
The literature on the nexus between finance and economic growth brings several results that support a long-term positive relationship between financial development and increases in the output of the economy. In order to test this interaction, we estimated a panel with fixed effects considering the 5,565 Brazilian municipalities in the period from 2003 to 2014. We verified that the relation between the credit growth rates and the average GDP per capita of the cities is positive and that the financial development variables generally have a positive impact on the volatility of economic growth. In addition, we found that the relationship between human development index and interest rate swings negatively correlates the economic growth of cities, which leads us to believe that greater wealth, on average, is related to GDP growth. However, we find that this effect is not so pronounced in wealthier cities, but they are more sensitive to changes in monetary policy.